Predictive Effect of Bone Conduction Pattern on Hearing Outcomes of Stapes Surgery. Issue 3 (16th March 2022) - Shapiro, Scott B.; Grojean, Meghan; Hong, Michael; Lipschitz, Noga; Breen, Joseph T.; Pensak, Myles L.; Samy, Ravi N.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Examine the effect of preoperative bone conduction pattern on outcomes of stapedotomy/stapedectomy. Study Design: Retrospective case series. Setting: Tertiary-care academic medical center. Patients: Patients who underwent stapedotomy or stapedectomy from 2013 to 2019. Interventions: Primary small-fenestra stapedotomy or partial stapedectomy. Main Outcome Measures: Association between preoperative bone conduction patterns and hearing after stapes surgery. Results: Complete audiometric data were available for 137 patients who had surgery. The mean preoperative air-bone gap (ABG) was 26.8 dBHL. The ABG was closed to less than 20 and 10 dBHL in 88.7 and 65.2% of patients, respectively. A notch at 2000 Hz was present in 32.1% of operated ears and was rarely found at other frequencies. There was no statistically significant association between the presence of a notch and hearing outcomes. The slope of the bone conduction line had no association with hearing outcomes, though an increased bone conduction PTA compared with the contralateral ear was associated with ABG closure less than 10 dBHL and overclosure (odds ratio: 2.14, p  = 0.027 and odds ratio: 2.20, p  = 0.04). Conclusion: In properly selected otosclerosis patients, depressions in bone conduction other than near 2000 Hz are rare and hearing outcomes are generally favorable regardless of the preoperative bone conduction pattern. Despite the association with otosclerosis, the presence of a notch at 2000 Hz is not associated with better hearing outcomes with surgery.